PERBEDAAN TINGKAT STRES PADA IBU RUMAH TANGGA YANG BEKERJA DAN IBU RUMAH TANGGA YANG TIDAK BEKERJA - Citra, Martha; Tetha Agustina, Menik (Berajah Journal, 2024)
Currently, many married women continue to perform their roles as housewives while also working. Being a working housewife is a suitable choice due to various factors, especially economic ones. There are many jobs that allow housewives to manage their time and responsibilities at home. This study aims to identify differences in stress levels between working and non-working housewives, as well as preventive measures to avoid depression that could impact the role of the mother at home. The focus of the research is on housewives aged 23 to 50, both working and non-working. This study uses a quantitative method with Multi Stage Random Sampling technique. A total of 40 samples were divided into two groups: non-working housewives and working housewives. The results showed that most items were rated very well by respondents, with some items showing strong positive or negative tendencies. Skewness analysis and percentage index provided additional insights into the validity and reliability of each item.